O modelowaniu rozwoju systemu wodnego w regionie rolniczym - Makowski, Marek (Wydział Prawa i Administracji UAM, 1978)
The paper deals with problems of modelling a water system expansion in an agricultural region. The model pertains to planning of a water system development and may be used for regional development analysis. For the latter application a concept of a family mutually linked models is discussed. Following other questions are considered in the paper: basic assumptions accepted for the region modelled, goal function that serves as a criterion for a water system development, the decisions variables, the structure of the model and the possibilities of the model application.
On Modelling a Water System Development in an Agricultural Region